UMPSA Vice-Chancellor joins Ziarah Kasih programme to support future UMPSA students - Naqiah, Puaad (UMPSA, 2025)
KUANTAN, 22 February 2025 – The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dr. Yatimah Alias, participated in the Ziarah Kasih programme by visiting and personally delivering offer letters to two future UMPSA students at their homes recently.